Mozambique - Analysis of Public Expenditure in Agriculture : Core Analysis - World Bank (World Bank, 2012)
The objective of this Agriculture Public Expenditure Review (AgPER) is to provide an assessment of the present situation and to offer recommendations to improve the effectiveness and efficiency of public spending in agriculture in Mozambique. The report provides a sectorwide picture of the magnitude and structure of public spending for agriculture in Mozambique over the past six years, and an overall assessment of the budget process in agriculture. It is intended that this analysis will inform future decisions over priority public expenditures for agriculture and the shifts in expenditure allocations and other measures that are necessary to make the most effective and efficient use of government budgetary resources and donors' contributions in the agriculture sector. The information is also meant to inform the New Partnership for Africa's Development (NEPAD) secretariat about the level and structure of spending in agriculture in Mozambique, and help the Ministry of Agriculture; since 2005 (MINAG) to report suitable figures to NEPAD. The report discusses the budget process in agriculture (budget planning, execution, and reporting) and the linkages between agricultural sector policies and strategy and public expenditures. It suggests possible ways to raise the effectiveness and efficiency of current public spending in agriculture, with a view to enhancing its contribution to Mozambique's economic growth and poverty reduction objectives. An analysis of the spatial pattern of expenditure is also provided. Some emphasis is placed on the adequacy of data sources and planning and on the budgeting procedures necessary in order to continuously align expenditure to objectives, and to maximize their impact. The report also draws some broad conclusions with regard to key options of agricultural policy on the basis of the data collected and available information on the relationship between costs and effects of selected activity strata.